Optimizing roasting time and temperature to enhance the physicochemical properties, and retention of bioactive compounds of three coffee arabica subvarieties - César R. Balcázar-Zumaeta; Katherine Reyna-Gonzales; Deysy Inga Diaz; Alexa J. Pajuelo-Muñoz; Angel F. Iliquin-Chavez; Ives Yoplac; Marleni Medina-Mendoza; Diner Mori-Mestanza; Ilse S. Cayo-Colca; Efraín M. Castro-Alayo (Applied Food Research)
The study optimized the roasting process of three arabica coffee subvarieties (Caturra, Catimor, and Typica) to enhance the physicochemical properties, while retaining bioactive compounds. For this, the response surface methodology with a central composite design was used to analyze three temperatures (140–220 °C) and times (2–10 min) of roasting. These roasting conditions retained key phenolic compounds such as chlorogenic, gallic, and caffeic acids and antioxidant compounds such as catechin and epicatechin. A reduction of the caffeine content was also observed. Likewise, the desirability compound (1.00) has allowed for optimizing the roasting process parameters; for instance, in the Caturra subvariety at 220 °C for 7.33 min based on a high Thb content. Optimal conditions for Thb and Thp in Catimor were found at 140 °C for 8.2 min and 144 °C for 10 min, respectively. In the Typica subvariety, the appropriate parameters are 161.8 °C for 2 min according to the Thp content. In conclusion, temperature and roasting time significantly impact coffee's chemical and functional properties, affecting the retention of key bioactive compounds and antioxidant capacity. By optimizing these parameters, it can be developed roasting profiles that enhance the nutraceutical benefits of different Arabica subvarieties, catering to consumers seeking coffee with improved health-promoting properties.